Climbing to the Top? Foreign Direct Investment and Property Rights - Ali, Fathi; Fiess, Norbert; MacDonald, Ronald (2012)
This article operates at the interface of the literature on the impact of foreign direct investment (FDI) on host countries and the literature on the determinants of institutional quality. We argue that FDI contributes to economic development by improving institutional quality in the host country. This proposition is tested within a large panel data set of 70 developing countries for the period 1981-2005. We show that FDI inflows have a positive and highly significant impact on property rights. Results are very robust and not affected by model specification, different control variables, or estimation technique. To our knowledge this is the first article to empirically test the FDI-property rights linkage.